PERSEPSI SIVITAS AKADEMIKA MUSLIM TERHADAP WAKAF UANG - Nurul Huda; Perdana Wahyu Sentosa; Novarini Novarini (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2019)
Abstract: The low collection of cash waqf is one of them due to the level of public understanding of cash waqf. This research aims to describe the characteristics of respondents based on the socio-economic demography of the Muslim Academic Community; and analyze of factors of influence people's perceptions of cash waqf in the Muslim Academic Community. The research method used is logistic regression analysis. The sample in this study were 138 respondents who were The Muslim Academic Community in Jabodetabek. The results showed that the respondents' characteristics of the sex of most women, aged between 20 years and less than 25 years, had income of less than Rp 3 million per month, were not married, had family members between 3 and 5 people, less than 2 people worked , have family responsibilities, students in university, have not worked, Private Universities in Central Jakarta, and the majority have never doing cash waqf. The results of the logistic regression analysis indicate that a person's level of faith and one's age can significantly influence perceptions of doing cash waqf. Keywords: Perception, Cash Waqf, Muslim Academic Community, Logistic Regression.